Regionalism and Memory Politics in Central Asia: Common or Competing Histories? - Waśkiel, Tomasz (Historia i Polityka, 2025)
The paper aims to examine the connection between historical narratives constructed by Central Asian states and the phenomenon of regionalism. It analyses how the elites refer to the shared historical legacy of the region and discusses selected historical disputes between states. Theoretical framework is based on the region-building approach. The concept of memory politics is significant for this study. Memory politics might contribute to the integration of society (or societies) and to the creation of collective identity (also regional). The main research method is discourse analysis. The paper focuses on statements of Kazakh and Uzbek presidents. The comparative method is adapted for the juxtaposition of the official historical narratives.